Staged Head and Neck Reconstruction: Heresy or a Reasoned Approach in a Select Group of Patients?. Issue 3 (September 2022) - Urken, Mark. L.; O'Malley, Quinn; Sandler, Mykayla; Xing, Monica H.; Ansari, Edward; Mundi, Neil; Buchbinder, Daniel; Alon, Eran; Okay, Devin
Study Design: case series. Objective: The restoration of defects in a single procedure with microvascular free flap reconstruction has become a mainstay of head and neck surgery. Yet in patients with complex defects and pre-existing comorbid medical conditions, a staged-reconstructive approach can enhance the safety of the procedure and improve the patient's outcome. Methods: We present 3 representative case examples of a larger series of patients who underwent reconstruction of major defects and discuss the usefulness of a staged-reconstructive approach in the management of complex patients. Results: All 3 patients, with an existing composite defect in the setting of prior radiation therapy, underwent successful staged-reconstructive surgery using a variety of free tissue and regional flap transfers. Conclusions: A staged approach facilitates the reconstruction of complex composite defects, increases vessel availability, and mitigates the risk of flap failure. Although this approach commits the patient to multiple procedures and a more prolonged plan of care, it is preferable to 1 operation in specific complex situations with adverse, high-risk clinical features.